Sebuah Tinjauan Literatur Sistematis: Dampak Mindful Learning Terhadap Keterampilan Metakognitif Siswa Sekolah Dasar - Westu Sedyo Kinasih; Ratna Hidayah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The lack of research on integrating mindful learning as a foundational approach to enhance metacognitive skills at the elementary school level presents a significant issue, given the critical role of metacognitive skills in academic preparedness. This study analyzes the impact of mindful learning on metacognitive skills through a systematic literature review of 8 journals (2016-2025). Results indicate that mindful learning-based interventions significantly improve metacognitive skills, particularly in learning strategy reflection and emotion regulation. Programs such as Paws b effectively enhance academic performance in students aged 7-9 through psychophysiological self-regulation mechanisms (top-down and bottom-up). Challenges include insufficient evidence of long-term effects and the need for cross-subject adaptation. Implementation requires curriculum integration, teacher training, and parental collaboration. The study concludes that integrating mindful learning in elementary education can optimize students' metacognitive skill development when supported by contextual intervention design and continuous evaluation. This research recommends policies prioritizing mindfulness-based teacher training and pilot programs across various educational levels.Kurangnya penelitian tentang integrasi mindful learning sebagai pendekatan dasar untuk meningkatkan keterampilan metakognitif tingkat sekolah dasar menjadi masalah penting, mengingat keterampilan metakognitif sangat krusial untuk kesiapan akademik. Penelitian ini menganalisis dampak mindful learning terhadap keterampilan metakognitif melalui metode systematic literature review dari 8 jurnal (2016-2025). Hasil menunjukkan intervensi berbasis mindful learning signifikan meningkatkan keterampilan metakognitif, terutama dalam refleksi strategi belajar dan regulasi emosi. Program seperti Paws b efektif meningkatkan prestasi akademik siswa usia 7-9 tahun melalui mekanisme regulasi diri (top-down dan bottom-up). Kendala meliputi kurangnya bukti efek jangka panjang dan kebutuhan adaptasi lintas mata pelajaran serta implementasi memerlukan integrasi kurikuler, pelatihan guru, dan kolaborasi orang tua. Simpulan penelitian menunjukkan bahwa integrasi mindful learning dalam pembelajaran dasar dapat mengoptimalkan perkembangan keterampilan metakognitif siswa ketika didukung oleh desain intervensi yang kontekstual dan evaluasi berkelanjutan. Penelitian ini merekomendasi perlunya kebijakan yang memprioritaskan pelatihan guru berbasis mindfulness dan program simulasi di berbagai jenjang satuan pendidikan.